ANALISIS WACANA KRITIS PEMBERITAAN RELOKASI WARGA PULAU REMPANG BATAM PADA MEDIA ONLINE TRIBUNBATAM.ID - Nawiyah, Siti; Malik, Abdul; Irawan, Dody (Universitas Sultan Ageng Tirtayasa, 2024)
This research discusses critical discourse analysis of reporting on the relocation of Rempang Island residents, Batam on the online media tribunbatam.id. The aim of this research is to describe the dimensions of critical discourse texts. The method used in the research is qualitative with a descriptive type. Research data collection techniques include news text documentation on the topic of news about the relocation of Rempang Island residents. The data analysis techniques in this research are data reduction, data presentation, and conclusions. The instrument in this research uses the critical discourse analysis method introduced by Teun A. van Dijk. The research results obtained from eight news texts about the relocation of residents of Rempang Island, Batam found elements in the text dimensions including theme, scheme, setting, details, intent, presuppositions, sentence form, coherence, pronouns, lexicon, and metaphor.